Comprehensive proteomic investigation of infectious and inflammatory changes in late preterm prelabour rupture of membranes - Vajrychová, Marie; Stráník, Jaroslav; Pimková, Kristýna; Barman, Malin; Kukla, Rudolf; Zedníková, Petra; Bolehovská, Radka; Plíšková, Lenka; Hornychová, Helena; Andrýs, Ctirad; Tambor, Vojtěch; Lenčo, Juraj; et al. (Scientific reports, 2020)
Preterm prelabour rupture of membranes beyond the 34th week of gestation (late PPROM) is frequently associated with the risk of the microbial invasion of the amniotic fluid (MIAC) and histological chorioamnionitis (HCA). Hence, we employed a Tandem Mass Tag-based approach to uncover amniotic fluid proteome response to the presence of MIAC and HCA in late PPROM. Protein dysregulation was associated with only five cases in the group of 15 women with confirmed MIAC and HCA. Altogether, 138 amniotic fluid proteins were changed in these five cases exclusively. These proteins were particularly associated with excessive neutrophil responses to infection, such as neutrophil degranulation and extracellular trap formation. We believe that the quantification of these proteins in amniotic fluid may assist in revealing women with the highest risk of excessive inflammatory response in late PPROM.
Keywords: Cohort Studies; Infant, Newborn; Chorioamnionitis; Humans; Female; předčasný odtok plodové vody; novorozenec; Proteomics; kohortové studie; lidé; ženské pohlaví; Pregnancy Complications, Infectious; těhotenství; Fetal Membranes, Premature Rupture; chorioamnionitida; infekční komplikace v těhotenství; dospělí; Pregnancy; Adult; proteomika